Aplikasi Absensi Siswa Magang Menggunakan Koordinat pada SMKN 1 Tanjung Jabung Timur - Heri Santoso; Kevin Kurniawansyah; Raja Aldi M.Arjun (Lembaga Pengembangan Kinerja Dosen, 2025)
Attendance is an activity carried out by a person to declare that he or she is present at a job or activity. SMKN 1 Tanjung Jabung Timur has an attendance process that is still done manually. This kind of absence has the weakness, namely that it allows damage to attendance papers and requires a long time in recapitulating and searching for data, and there is fraud from students who fill in attendance not at the designated internship location because they are not monitored directly. Based on this problem, researchers are interested in building a coordinate attendance system application using GPS that can solve this problem. With this attendance, it is also easier, faster and more effective for students to fill in the attendance list without cheating. This attendance uses GPS Lock and the Havershine formula algorithm to determine the location with high accuracy and calculates a maximum distance of 20 meters from the specified coordinate point. The results and benefits of the attendance application using coordinates for internship students at SMKN 1 Tanjung Jabung Timur are that it facilitates the attendance process between students and teachers, reduces fraud that occurs, and avoids damage to attendance data so that it can produce more accurate reports.